TEACHING ENGLISH THROUGH STORYTELLING - Mahmudov Khurshed Farhodzod, (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Storytelling is one of the most effective and natural techniques for teaching English as a foreign language. It blends language, culture, and creativity while helping learners enhance their listening, speaking, reading, and writing skills. This article examines the pedagogical benefits of storytelling, its application in the language classroom, and how it can foster both linguistic competence and emotional engagement. A minimized version of the story “Hellados”[1] is included, followed by exercises to reinforce vocabulary and comprehension. [1] Hellados written by Nodar Dumbadze